Організація обліку. Облік і звітність в оподаткуванні на прикладі ТОВ «Фрідом Фарм Терра» - Малімонова, С. М. (My University, 2018)
UK: Досліджено теоретичні питання організації обліку та питання обліку і звітності в оподаткуванні на прикладі ТОВ «Фрідом Фарм Терра». EN: Theoretical issues of accounting organization and issues of accounting and reporting in taxation on the example of LLC "Freedom farm Terra" are Investigated.
The organization of accounting. Accounting and reporting in taxation on the example of "Freedom Farm Terra"
Keywords: підприємство; бухгалтерський облік; організація; податки; компанія; enterprise; accounting; organization; taxes; company